1993
DOI: 10.1111/j.1476-5381.1993.tb13509.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐induced airway hyperresponsiveness in the guinea‐pig: possible involvement of histamine and inflammatory cells

Abstract: 1 Guinea-pig tracheal contractions by histamine and by the cholinoceptor agonist, arecoline, are significantly enhanced (30% and 20%, respectively), 96 h after intra-tracheal inoculation with Parainfluenza-3 (PI-3) virus. 2 The airway hyperresponsiveness in animals inoculated with virus coincides with a significant increase in the number of broncho-alveolar cells (82%), and in the albumin concentration (121%) in lung lavage fluid, relative to values obtained in guinea-pigs challenged with control solution. 3 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…In patients infected with respiratory syncytial virus, the release of histamine in nasopharyngeal secretions was detected significantly more often and in higher concentrations in patients with wheezing (37). Histamine concentrations are increased in the broncho-alveolar lavage fluid of PI-3 virus-treated guinea pigs (6) and antiallergic drugs and antihistamines can prevent the virus-induced airway hyperresponsiveness and influx of inflammatory cells (27). Therefore, a number of processes may act additively or synergistically during the development of airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In patients infected with respiratory syncytial virus, the release of histamine in nasopharyngeal secretions was detected significantly more often and in higher concentrations in patients with wheezing (37). Histamine concentrations are increased in the broncho-alveolar lavage fluid of PI-3 virus-treated guinea pigs (6) and antiallergic drugs and antihistamines can prevent the virus-induced airway hyperresponsiveness and influx of inflammatory cells (27). Therefore, a number of processes may act additively or synergistically during the development of airway hyperresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Growth medium was treated identically. Previous experiments have shown that PI-3 virus could be isolated from the airways of all guinea-pigs 2 days after infection (Folkerts et al, 1993a).…”
Section: Virus Inoculationmentioning
confidence: 97%
“…On the other hand, Santing et al (23) described the contribution of histamine to the development of the late asthmatic reaction as well as to early and late bronchial hyperreactivity. Histamine does not directly increase the responsiveness of guinea pig trachea; however, histamine may be involved in a cascade of events leading to airway hyperresponsiveness (24). Although a clear explanation has not been reported regarding the involvement of histamine in the development of airway hyperresponsiveness, the present study indicates that histamine contributes to LPA-induced airway hyperresponsiveness based on the effectiveness of antihistaminics and the in vitro experiment.…”
Section: Discussionmentioning
confidence: 66%